JOURNAL OF GOVERNMENT & POLITICS : Does Democracy Make You Happy? Multilevel Analysis of self-rated Happiness in Indonesia - Sujarwoto (FISIPOL UMY, 2016)
The linkage between democracy and citizen happiness in developing countries is rarely